Impact of Human Resource Management Governance (HRMG) on achieving Organizational Happiness (OS) at Public Sector Organizations in Jordan - Dr. Haitham Ali Hijazi * (مجلة الدراسات الاقتصادية والادارية)
The study aimed to identify the impact of human resource management governance on achieving organizational happiness in public sector institutions in Jordan. The study population consisted of government sector employees classified in the first and second categories subject to the civil service bylaw, numbering (181,989) employees, and the sample size of the study was (279) employees. The study followed the descriptive-analytical approach, and concluded that there is a statistically significant impact for human resource management governance on achieving organizational happiness in the researched sector. The study recommended that public sector institutions in Jordan convert the principles of human resource governance into strategies that are implemented, with the aim of supporting employee satisfaction and enhancing institutional performance, instead of those principles being a mere organizational process.